Investigação epidemiológica de Borrelia burgdorferi em equinos do município de Sinop, estado de Mato Grosso, Brasil - Socoloski, Suyane Nayara Garcia (2017)
Borrelia burgdorferi sensu stricto is the main etiologic agent of Lyme disease (LD) in the United States of America (USA). In Brazil, a variant genetically similar to this spirochete is believed to be the causative agent of Baggio-Yoshinari Syndrome (BYS), a Brazilian emerging zoonosis, transmitted by ticks, that presents clinical manifestations similar to LD. Equines are indicated as important hosts in the transmission chain and in the maintenance of this spirochete in the country. Therefore, the aim of this study was to detect the frequency of homologous antibodies of the class. IgG anti-B. burgdorferi American strain G39/40, in horses of the municipality of Sinop - MT, by means of a seroepidemiological survey using the indirect Enzyme-Linked Immunosorbent Assay (ELISA) as diagnostic test. Blood samples were collected from 367 horses from 81 properties of Mato Grosso. It was also applied an epidemiological survey conducted during visits, obtaining identification information and characterization of the animals and their properties. From the 367 samples submitted to serological analysis, 214 were positive according indirect ELISA for B. burgdorferi sensu stricto, determining an apparent prevalence of 54.04%. Concomitantly, from the 367 horses evaluated, whole blood samples from 89 animals were submitted to biomolecular analysis by the nested-Polymerase Chain Reaction (PCR). According to the PCR test, none of the samples were positive in this test. Considering these 89 animals tested, 53 were positive in the indirect ELISA and 36 negative. From the 81 analyzed properties, 75 (92.59%) had at least one B. burgdorferi seropositive equine, of which about 89% presented pastures near the forest, which predisposes the contact of the horses with wild animal species and ticks. The results support the hypothesis of the presence of anti-Borrelia spp. in the state of Mato Grosso.